A study on the low-temperature wet synthesis of hydrofluoric acid from synthetic calcium fluoride and waste sulfuric acid. Issue 1 (March 2020) - Lin, Min-Fa; Chang, Chih-Ping; Chang, Ken-Lin; Lee, Wen-Jhy; Wu, Jhong-Lin; Chen, Po-Han
Abstract: An innovative method for utilizing synthetic calcium fluoride (CaF2 ), recovered from fluoride-containing semiconductor wastewater, and waste sulfuric acid (H2 SO4 ) to produce hydrofluoric acid (HF) was investigated. The research was set to study the low-temperature production of HF via the reaction of synthetic CaF2 and waste H2 SO4 . The impact of H2 SO4 concentration and total volume (H2 SO4 + H2 O)/CaF2 ratio, drying temperature of synthetic CaF2 on HF productivity were investigated in this study. HF yield increased with increasing H2 SO4 concentration and total volume/CaF2 ratio under room temperature. In addition, the HF produced in the reactions involving the 105 °C-dried synthetic CaF2 were higher than the 600 °C-dried synthetic CaF2 ones. The study will not only find uses for this semiconductor wastes but also provide a greener alternative to the current commercial production of HF.